DNA replication roadblocks caused by Cascade Interference complexes are alleviated by RecG DNA repair helicase - Killelea, Tom; Hawkins, Michelle; Howard, Jamieson; McGlynn, Peter; Bolt, Edward L. (Taylor & Francis, 2018)
Cascade complexes underpin E. coli CRISPR-Cas immunity systems by stimulating "adaptation" reactions that update immunity and by initiating "interference" reactions that destroy invader DNA. Recognition of invader DNA in Cascade catalysed R-loops provokes DNA capture and its subsequent integration into CRISPR loci by Cas1 and Cas2. DNA capture processes are unclear but may involve RecG helicase, which stimulates adaptation during its role responding to genome instability. We show that Cascade is a potential source of genome instability because it blocks DNA replication and that RecG helicase alleviates this by dissociating Cascade. This highlights how integrating in vitro CRISPR-Cas interference and adaptation reactions with DNA replication and repair reactions will help to determine precise mechanisms underpinning prokaryotic adaptive immunity.